SCHIZOAFFECTIVE DISORDER WITH MANIC TYPE : A CASE REPORT - A.A. Gede Ocha Rama Kharisma Putra (E-Jurnal Medika Udayana, 2014)
Schizoaffective disorder is a disease with persistent psychotic symptoms, such ashallucinations or delusions, occurs together with mood disorder such as depression,manic, or mixed episodes. Schizoaffective disorder is estimated to occur morefrequently than bipolar disorder. A psychotic disorder with symptoms of schizophreniaand manic air equally prominent in one episode of the same disease. This reportdescribes the case of b schizoaffective disorder with manic type in women aged 42years. These patients get therapy is pharmacotherapy Carbamazepine 2x200 mg orallyand Stelazine 2x5 mg orally.